Predicting the crack path in a wedge under a concentrated tensile force by means of variational principle (Fracture and Structural Integrity, 2019)
Variational principle of brittle fracture mechanics is employed to predict the crack path in an infinite wedge under a concentrated tensile force. The weight function in basic equation of variational problem is assumed to be proportional to the maximum strain in the uncracked wedge. Obtained equation for solving the variational problem allowed predicting the crack path in general. The predicted crack path is in agreement with experimental results obtained in the case of the truncated wedge.
Keywords: Crack path; Variational principle; wedge; Concentrated tensile force